A study on morbidity profile of lignite miners in western India - Nandi, Subroto; Dhatrak, Sarang V; Chaterjee, Debasis M; Dhumne, Umesh L; Ingole, Shilpa V (International Journal of Occupational Safety and Health, 2017)
Background: Mining is a hazardous occupation in which workers are exposed to adverse conditions. In India, there are nine working lignite mines, producing about 30 million tons annually. The mines are located in the states of Tamilnadu, Rajasthan and Gujrat. Objective: The present study was carried out in a lignite mine in India to determine the health status of the miners. Methods: 143 workers engaged actively in mining activities were included. The health status of the employees was evaluated by well defined medical questionnaire along with pulmonary function test (PFT) and Audiometry. Result: Findings of the study showed poor literacy rate amongst the miners. Pulmonary impairment was present in 11.88% and noise induced hearing impairment in about 12.15% of the miners. Conclusion: The study findings indicate the need for regular health checkups, health education, personal protective devices and engineering control.